2019
DOI: 10.1186/s12882-019-1221-5
|View full text |Cite
|
Sign up to set email alerts
|

Magnesium lithospermate B improves renal hemodynamics and reduces renal oxygen consumption in 5/6th renal ablation/infarction rats

Abstract: BackgroundMagnesium lithospermate B (MLB) can promote renal microcirculation. The aim of the current project was to study whether MLB improves renal hemodynamics, oxygen consumption and subsequently attenuates hypoxia in rats induced by 5/6th renal Ablation/Infarction(A/I).MethodsChronic renal failure (CRF) was induced in male SD rats by the 5/6 (A/I) surgery. 30 rats were randomly divided into three groups: sham group, 5/6 (A/I) + vehicle group (CRF group) and 5/6 (A/I) + MLB (CRF + MLB) group. 28 days after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 15 publications
0
12
0
Order By: Relevance
“…Therefore, the inhibition of TGF-β signaling has received attention as a potential and useful therapy for pulmonary fibrosis [ 40 , 41 ]. Magnesium lithospermate B (MLB) has been reported to have anti-inflammatory, antioxidative and antifibrotic effects, especially in experimental models of liver fibrosis and renal or cardiovascular diseases, with great safety and tolerance [ 27 , 30 , 42 ]. More alternatives to treatments for pulmonary fibrosis will be provided if MLB is validated for alleviating pulmonary fibrosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the inhibition of TGF-β signaling has received attention as a potential and useful therapy for pulmonary fibrosis [ 40 , 41 ]. Magnesium lithospermate B (MLB) has been reported to have anti-inflammatory, antioxidative and antifibrotic effects, especially in experimental models of liver fibrosis and renal or cardiovascular diseases, with great safety and tolerance [ 27 , 30 , 42 ]. More alternatives to treatments for pulmonary fibrosis will be provided if MLB is validated for alleviating pulmonary fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous research reported the protective and anti-inflammation effects of MLB on hepatic ischemia/reperfusion [ 28 ]. Other previous studies have shown that MLB might effectively attenuate liver or renal fibrosis by inhibiting the TGF-β pathway [ 29 , 30 , 31 ]. The severity and mortality of IPF patients are worse than those of patients with other forms of tissue fibrosis because of the high risk of the acute exacerbation of IPF and subsequent respiratory failure [ 32 ], and more alternatives for pulmonary fibrosis therapies will be available if MLB can effectively alleviate pulmonary fibrosis [ 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…Compared with intravenous injection and conventional liposomes, long-circulating liposomes of Sal B prolong the retention time and drug concentration of Sal B in liver, kidney, and brain, showing higher bioavailability ( Pi et al, 2015 ). Sustained release of Sal B using scaffolds has also shown to enhance the osteogenic differentiation and osteogenesis of MSCs during spinal fusion or repair of bone tissue defects ( Li et al, 2016 ; Lin et al, 2019 ). The current multidisciplinary research provides more possibilities for improving the bioavailability of Sal B, which needs more cooperation in disciplines such as biomaterials and medicinal chemistry.…”
Section: Low Bioavailability Of Salvianolic Acid Bmentioning
confidence: 99%
“…The officinal parts of Salvia miltiorrhiza Bunge are the root and rhizome. Salvia miltiorrhiza Bunge and its extractions have been shown to reduce proteinuria and attenuate kidney injury in several animal models of kidney disease, including 5/6th renal ablation/infarction ( Lin et al, 2019a ), renal ischemic reperfusion injury ( Ma et al, 2017 ), diabetic nephropathy ( Hou et al, 2017 ), and doxorubicin-induced nephropathy ( Liu et al, 2011 ). These effects associated with anti-inflammatory and antioxidative mechanisms have been observed in conjunction with these observed beneficial effects.…”
Section: Mechanisms Of Chinese Herbal Medicines In Treating Kidney DImentioning
confidence: 99%